a.
[tex]lim _{x \to 2} \frac{x-2}{\sqrt{x+2}-2}=lim_{x \to 2}\sqrt{x+2}+2=4=f(2)[/tex]
Hàm liên tục tại x=2
b.
[tex]lim_{x \to -2}\frac{x^2-3x-10}{x+2}=lim_{x \to -2}(x-5)=-7\\f(-2)=-4(m-1)[/tex]
Để hàm liên tục tại x=-2 thì -4(m-1)=-7 =>m=...
c.
[tex]lim_{x \to 3}\frac{-x^3+5x^2-5x-3}{2x^2-x-15}=lim_{x \to 3}\frac{-(x-3)(x^2-2x-1)}{(x-3)(2x+5)}=lim_{x \to 3}\frac{-x^2+2x+1}{2x+5}=\frac{-2}{11}=f(3)=\frac{-2}{11}[/tex]
Hàm liên tục tại x=3
d.
[tex]lim_{x \to -1^+}\frac{2x^2-x-3}{x^2+x}=lim_{x \to -1^+}\frac{(2x-3)(x+1)}{x(x+1)}=lim_{x \to -1^+}\frac{2x-3}{x}=5\\f(-1)=lim_{x \to -1^-}f(x)=-2m+1[/tex]
Để hàm liên tục tại x=-1 thì -2m+1=5 -> m=-2